OPOSISI BINER ILMU PENGETAHUAN DALAM ISLAM (SEBUAH REFLEKSI PENDIDIKAN MASA KINI) - Muchdor, Ahmad; Gufron, Iffan Ahmad (Institut Agama Islam Ngawi, 2024)
In this article, we will explore the dualistic paradigm of Islamic science, characterized by the separation of religious awareness from general education. Examine the emergence of the binary opposition, the historical process, and its impact on Islamic society. Historically, the origins of this binary opposition in science lie in the period when Islam came into contact with other cultures. This continued to develop and eventually led to a dichotomy between popular scientific thought and religion. The result of this contrast is clearly visible, namely that Islamic society is increasingly lagging behind Western civilization whose effects are still felt today. This research was compiled using descriptive analysis techniques, namely by examining several books and articles as primary sources. This research was conducted to reflect on the problems of Islamic education, whether there is still a dichotomy between science and religion or starting to rise to integrate the two. Keywords: Dichotomy, integration, science